Systematic Review on the Efficacy and Safety of Oral Janus Kinase Inhibitors for the Treatment of Atopic Dermatitis - Le, Michelle; Berman-Rosa, Melissa; Ghazawi, Feras M.; Bourcier, Marc; Fiorillo, Loretta; Gooderham, Melinda; Guenther, Lyn; Hanna, Sameh; Hong, H. Chih-Ho; Landells, Ian; Lansang, Perla; Marcoux, Danielle; et al. (Frontiers in Medicine, 2021)
Background: Atopic dermatitis is a chronic, relapsing and remitting disease that can be difficult to treat despite a recently approved biologic therapy targeting IL-4/IL-13 receptor. Oral janus kinase inhibitors (JAKi) represent a novel therapeutic class of targeted therapy to treat moderate-to-severe atopic dermatitis (AD). Objective: To review the efficacy, safety, and pharmacokinetic characteristics of oral JAKi in the treatment of AD. Methods: A PRISMA systematic review was conducted using MEDLINE, EMBASE (Ovid), and PubMed databases for studies assessing the efficacy, safety, and/or pharmacokinetics of oral forms of JAKi in the treatment of AD in pediatric or adult populations from inception to December 2020. Results: 367 papers were reviewed. Of 21 articles that underwent full text screening, 8 met our inclusion criteria for final qualitative review. Three studies examined abrocitinib; three studies examined baricitinib; one examined gusacitinib (ASN002), and another upadacitinib. Significant clinical efficacy and a reassuring safety profile was reported for all JAKi agents reviewed. Rapid symptom control was reported for abrocitinib and baricitinib. Limitations: Given the relatively limited evidence for each JAKi and the differences in patient eligibility criteria between studies, the data was not deemed suitable for a meta-analysis at this time. Conclusion: Given their ability to achieve rapid symptom control with a reassuring safety profile, we recommend considering the use of JAKi as a reliable systemic treatment option for adult patients with moderate-to-severe AD, who are unresponsive to topical or skin directed treatments.